2017
DOI: 10.32508/stdjns.v1it2.450
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of NIN-like protein (NLP) family in maize (Zea mays L.) by using bioinformatic methods

Abstract: The NIN-like proteins (NLP) belong to RWP-RK transcription factor family and possess the similarity characteristics of NIN (Nodules INception). The NLPs regulate the expression of genes which are involved in nitrate signaling in plants. In this work, we have performed a genome-wide analysis of the NLP gene family in maize (Zea mays L.) through the bioinformatic methods. We identified a total of nine NLP encoding genes in whole genome of maize. The genomic sequences of these genes were from 2855 to 8092 nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Accordingly, the number of exons varies between 3 and 6, while the number of introns varies between 2 and 5. Similar to the Pvul-NIN genes, in a previous report by Cho (2017) on Zea mays, it was observed that the exon and intron structures of 9 NIN genes were found in similar numbers to the ones in this study, the number of exons varied between 4 and 5, while the number of introns varied between 3 and 4 [62]. Phylogenetic analysis was performed to understand and compare the evolutionary relationship between Pvul-NIN and Arabidopsis (non-nodulating) and NIN genes belonging to G. max (Nodulator).…”
Section: Structure Of Pvul-nin Genes Phylogenetic Tree Analysis Deter...supporting
confidence: 88%
“…Accordingly, the number of exons varies between 3 and 6, while the number of introns varies between 2 and 5. Similar to the Pvul-NIN genes, in a previous report by Cho (2017) on Zea mays, it was observed that the exon and intron structures of 9 NIN genes were found in similar numbers to the ones in this study, the number of exons varied between 4 and 5, while the number of introns varied between 3 and 4 [62]. Phylogenetic analysis was performed to understand and compare the evolutionary relationship between Pvul-NIN and Arabidopsis (non-nodulating) and NIN genes belonging to G. max (Nodulator).…”
Section: Structure Of Pvul-nin Genes Phylogenetic Tree Analysis Deter...supporting
confidence: 88%